Plots, Concubines and Fight for Income in the Diocese of Segovia during the Thirteenth Century (Edad Media. Revista de Historia, 2018)
During the first half of the thirteenth century, the members of the Diocese of Segovia, bishop and clergy, clashed in a fight without solution that revolved around the distribution of income coming from the ecclesiastical dominion. However, the documents extant in the Archives of the Cathedral and of the Diocese of Segovia show that the confrontation went beyond a local economic dispute relating the jurisdictional sphere, and transcended to the social relations of the Segovian clergy and the mentality attached to them.
Keywords: Income; Segovia; Cardinal Gil Torres; Concubines; Mistresses; Fourth Lateran Council; Diocese of Segovia